Desmoglein 2 regulates cardiogenesis by restricting hematopoiesis in the developing murine heart - Hoda Moazzen (Nature Portfolio, 2021)
Abstract Cardiac morphogenesis relies on intricate intercellular signaling. Altered signaling impacts cardiac function and is detrimental to embryonic survival. Here we report an unexpected regulatory role of the desmosomal cell adhesion molecule desmoglein 2 (Dsg2) on murine heart development. A large percentage of Dsg2-mutant embryos develop pericardial hemorrhage. Lethal myocardial rupture is occasionally observed, which is not associated with loss of cardiomyocyte contact but with expansion of abnormal, non-myocyte cell clusters within the myocardial wall. Two types of abnormal cell clusters can be distinguished: Type A clusters involve endocard-associated, round-shaped CD31+ cells, which proliferate and invade the myocardium. They acquire Runx1- and CD44-positivity indicating a shift towards a hematopoietic phenotype. Type B clusters expand subepicardially and next to type A clusters. They consist primarily of Ter119+ erythroid cells with interspersed Runx1+/CD44+ cells suggesting that they originate from type A cell clusters. The observed pericardial hemorrhage is caused by migration of erythrocytes from type B clusters through the epicardium and rupture of the altered cardiac wall. Finally, evidence is presented that structural defects of Dsg2-depleted cardiomyocytes are primary to the observed pathogenesis. We propose that cardiomyocyte-driven paracrine signaling, which likely involves Notch1, directs subsequent trans-differentiation of endo- and epicardial cells. Together, our observations uncover a hitherto unknown regulatory role of Dsg2 in cardiogenesis.